The role of Nykyfor Hryhoriyv in the organizational and educational activities of the Ukrainian Public Committee in the Czechoslovak Republic. - Sukhobokova , Olga (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2023)
Purpose. Analysis of Nykyfor Hryhoriyv’s contribution to the organizational and educational activities of the Ukrainian Public Committee in the Czechoslovak Republic. The research methodology is based on the principles of historicism, objectivity and systematicity. The use of problem-chronological and complex approaches, comparative and analytical methods made it possible to determine the conceptual foundations and practical implementation of N. Hryhoriyv’s vision of building a Ukrainian educational center in the Czechoslovak Republic. Scientific novelty. For the first time, the organizational activity of Nykyfor Hryhoriyv in the Ukrainian Public Committee in the field of Ukrainian education in the Czechoslovak Republic is holistically considered as a separate subject of research. The relevance of the research is determined by the formulation of the question and its comprehensive consideration within specific chronological and spatial boundaries. His efforts in the organization of Ukrainian higher educational institutions under the Ukrainian Public Committee (Ukrainian Academy of Economics in Podyebrady and Ukrainian Higher Pedagogical Institute named after M. Drahomanov in Prague), professional education within the framework of the Ukrainian Peasant Union and publication of educational literature are considered as purposeful work on the formation of national-patriotic position of the Ukrainian community in exile and the training of a new generation of fighters for the independence of Ukraine. Conclusions. The organizational and educational activity of Nykyfor Hryhoriyv, as one of the founders and leaders of the Ukrainian Public Committee in the Czechoslovak Republic, was an organic continuation of his previous activities and the course of uniting Ukrainians abroad around one of the priority tasks of social construction – the formation of the future intellectual and professional elites, builders of the Ukrainian state, primarily teachers and specialists in various branches of the economy. Thus, according to his conviction, Ukrainian refugees acquired a European-level education with Ukrainian national-patriotic education and specialties needed for their homeland. And therefore, they used the time of their stay in emigration with the greatest benefit for the future development of their homeland.